PELATIHAN PEMBUATAN SUSU GORENG DARI SUSU SEGAR KEPADA IBU PKK DI NAGARI TALAWI MUDIAK - Komala, Refika; andi, Andi alatas; Supriyanti, Juli; Hendrita, Vivi; Jarlis, Roni; Arief Syuhada, Fildza; Ananto, Ananto; Meidita, Fadilla (Fakultas Pertania Universitas Muara Bungo, 2023)
ABSTRACT The aim of this community service is to increase the knowledge and skills of PKK women who use animal protein as a food source to prevent stunting and as a trading business in Talawi Mudiak Village, Talawi District, Sawahlunto City. The methods used in this service are lectures, discussions and demonstrations while the stages start with presentation of the material, training in making fried milk, as well as the evaluation stage. The results of this training are based on the results of answers to questions directly after completing the practice, that the PKK women who participated in this service were able to mention the process and ingredients needed to make fried milk and there were no obstacles in the making process. Apart from that, service participants are also able to make fried milk independently. Keywords Cow's milk; Fried milk, Training